2012
DOI: 10.5194/hess-16-3101-2012
|View full text |Cite
|
Sign up to set email alerts
|

Water resources trends in Middle East and North Africa towards 2050

Abstract: Abstract. Changes in water resources availability can be expected as consequences of climate change, population growth, economic development and environmental considerations. A two-stage modeling approach is used to explore the impact of these changes in the Middle East and North Africa (MENA) region. An advanced, physically based, distributed, hydrological model is applied to determine the internal and external renewable water resources for the current situation and under future changes. Subsequently, a water… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(103 citation statements)
references
References 36 publications
2
101
0
Order By: Relevance
“…PCR-GLOBWB is used at a global scale for a variety of purposes: seasonal prediction, quantification of the hydrological effects of climate variability and climate change, to compare changes in terrestrial water storage with observed anomalies in the Earth's gravity field and to relate demand to water availability in the context of water scarcity (see Sperna Weiland et al, 2012;Wada et al, 2011;Droogers et al, 2012;Sperna Weiland et al, 2011).…”
Section: Pcr-globwbmentioning
confidence: 99%
“…PCR-GLOBWB is used at a global scale for a variety of purposes: seasonal prediction, quantification of the hydrological effects of climate variability and climate change, to compare changes in terrestrial water storage with observed anomalies in the Earth's gravity field and to relate demand to water availability in the context of water scarcity (see Sperna Weiland et al, 2012;Wada et al, 2011;Droogers et al, 2012;Sperna Weiland et al, 2011).…”
Section: Pcr-globwbmentioning
confidence: 99%
“…Water desalination has become a technologically and economically viable solution to tackle the challenges associated with increasing water shortages existing in many regions of the world [1,2]. Yet, desalination is an energy intensive process normally requiring high tonnage plants that utilize expensive and non-renewable fossil fuels, which in turn contribute to global warming and air pollution [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Aquifer salinization and pollution are leading to the degradation of water resources and the situation is expected to worsen with growing populations and climate change (Qadir et al 2009;Droogers et al 2012). Additionally, challenges in coping with water demands are leading to shortages in food and energy according to recent reports by the United States Intelligence Community (USIC 2012).…”
Section: Introductionmentioning
confidence: 99%